(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2024)
Stunting, as a chronic nutritional problem that inhibits optimal child growth, has a significant impact on Indonesia’s demographic bonus potential. In Indonesia, the prevalence of stunting reached 24.4% in 2021, with long-term impacts including cognitive decline, low productivity, and increased risk of chronic diseases. Health Monitoring application for the detection and prevention of stunting in early childhood. Using the waterfall method, this research produced an application with seven main pages that allow comprehensive monitoring of child growth. Functionality testing showed a 95% success rate in implementing critical features, including navigation, authentication, and child data management. Feedback from 50 early adopters showed an 85% satisfaction rate and a 40% increase in the frequency of child growth monitoring. Key challenges included cross-platform data integration and performance optimization on low-specification devices, which were addressed through the development of a modular architecture and code optimization. The app has the potential to increase early detection of growth problems by 30%, enabling timely interventions to improve children’s long-term health outcomes. Implementation simulations show a potential reduction in stunting prevalence of 5% within 3 years if widely used. Although limited to user interface development, this research lays the foundation for further development, including the integration of advanced data analysis and nutrition improvement features, which are projected to increase the effectiveness of stunting detection and intervention by up to 50%.